2014
DOI: 10.2172/1136112
|View full text |Cite
|
Sign up to set email alerts
|

Flowsheet Modification for Sodium Reactor Experiment and Denmark Reactor-3 Used Nuclear Fuel Processing

Abstract: Flowsheet parameters for the dissolution of SRE/DR-3 fuel include the following. The Hg catalyst is added gradually after the dissolver has reached temperature to achieve a maximum catalyst concentration of 0.012-0.015 M. The initial nitric acid concentration is in the range of 6-7 M and dependent on the amount of Al, Th, and U to be dissolved, targeting a final nitric acid concentration of 0.5-1.0 M after completion of the dissolution of the last charge. Boric acid (H 3 BO 3) or gadolinium nitrate (Gd(NO 3) 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 4 publications
2
16
0
Order By: Relevance
“…The results from this study and previous studies 1,2,21,22 have demonstrated that Al alloys containing smaller amounts of alloying elements (e.g., Fe, Mg, Si, etc.) dissolve at a faster rate.…”
Section: Recommendationssupporting
confidence: 80%
See 1 more Smart Citation
“…The results from this study and previous studies 1,2,21,22 have demonstrated that Al alloys containing smaller amounts of alloying elements (e.g., Fe, Mg, Si, etc.) dissolve at a faster rate.…”
Section: Recommendationssupporting
confidence: 80%
“…In this and in previous studies, 1,2,21,22 variations in the dissolution rates of different Al alloys were observed. Both Al-1100 and Al-6063, including the L-Bundle End Cap sidewall, had similar dissolution rates that were much greater than measured for Al-6061.…”
Section: Probable Contributors To H-canyon Dissolution Rate Variabilisupporting
confidence: 80%
“…Bundles of SNF containing U-Al assemblies are currently dissolved using a Hg-catalyzed, HNO 3 flowsheet. 8,9 The Hg catalyst is added gradually after the dissolver has reached the solution boiling point to achieve a maximum catalyst concentration of 0.012 -0.015 M; a Hg concentration of 0.002 M Hg was previously used to dissolve foreign and domestic research reactor fuels prior to implementation of the current flowsheets. 8 The initial HNO 3 concentration is dependent on the amount of Al and U to be dissolved, targeting a final HNO 3 concentration of 0.5-1.0 M after completion of the dissolution of the last charge.…”
Section: Figure 1-2 Hfir Insertmentioning
confidence: 99%
“…The H 2 generation rate per unit surface area is plotted as a function of the dissolved Al concentration in Figure 3-1 for both alloys. The concentration of Al in the dissolving solution as a function of time was estimated using the method described by Almond et al 8 The plot shows that the dissolution of the Al 1100 alloy is bounding in terms of the H 2 generation rate when compared to the dissolution of the Al 6061 T6 alloy. Based on these results, data from the dissolution of Al 1100 were used to evaluate the H 2 generation rate from the dissolution of HFIR fuel.…”
Section: Review Of Past Hfir Fuel Dissolution Campaignsmentioning
confidence: 99%
See 1 more Smart Citation